Additive Manufacturing of Poly(propylene) by Means of Melt Extrusion. Issue 12 (29th September 2016) - Hertle, Sebastian; Drexler, Maximilian; Drummer, Dietmar
Abstract : The approach of additive manufacturing of semicrystalline thermoplastics with melt extrusion is addressed in this paper. Due to the use of standard granules in an extrusion system, a high polymer variety is provided. The investigations focus on temperature induced conditions and fast solidification on mechanical part properties as well as on morphological behavior. Abstract : Additive manufacturing (AM) processes can provide great input for solving recently encountered challenges of the global market such as mass customization, highly dynamic environments, and the decrease of time needed from a draft to final products. This study aims at contributing to the issue of material limitations typically present in AM by researching possibilities of directly using technically relevant and commercially available polymer granules in melt extrusion processes. In order to extend the knowledge on the processing of semicrystalline polymers in melt extrusion based processes, different temperature induced influences on mechanical and morphological properties are investigated for poly(propylene). Mechanical tests are conducted to evaluate the effects and interdependencies of substrate, extrusion, and cooling temperature. Finally, based on the identified mechanical and rheological behavior of the material, a process window for the used materials is suggested.